2019
DOI: 10.1074/jbc.ra119.007831
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analyses reveal that a glucuronoyl esterase from Teredinibacter turnerae interacts with carbohydrates and aromatic compounds

Abstract: Glucuronoyl esterases (GEs) catalyze the cleavage of ester linkages found between lignin and glucuronic acid moieties on glucuronoxylan in plant biomass. As such, GEs represent promising biochemical tools in industrial processing of these recalcitrant resources. However, details on how GEs interact with their natural substrates are sparse, calling for thorough structure-function studies. Presented here is the structure and biochemical characterization of a GE, Tt CE15A, from the bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…Substitution of either the catalytic serine (Ser-267) or histidine (His-408) with alanine significantly compromised the Ot CE15A turnover rate ( k cat ), reducing the rate by 17,000- and 1,700-fold, respectively. Compared with the Tt CE15A S281A variant, where the k cat only decreased 370-fold (11), the S267A variant of Ot CE15A was dramatically crippled. Ot CE15A is an interesting member of CE15 and the α/β-hydrolase superfamily in that it features acidic residues at both the canonical and noncanonical positions (Glu-290 and Asp-356) (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Substitution of either the catalytic serine (Ser-267) or histidine (His-408) with alanine significantly compromised the Ot CE15A turnover rate ( k cat ), reducing the rate by 17,000- and 1,700-fold, respectively. Compared with the Tt CE15A S281A variant, where the k cat only decreased 370-fold (11), the S267A variant of Ot CE15A was dramatically crippled. Ot CE15A is an interesting member of CE15 and the α/β-hydrolase superfamily in that it features acidic residues at both the canonical and noncanonical positions (Glu-290 and Asp-356) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In recent work, we have revealed that some bacterial CE15 members have more promiscuous substrate specificities, where certain enzymes are able to hydrolyze both glucuronoate and galacturonoate (GalA) esters (7). The first structurally and biochemically characterized CE15 members were of fungal origins, and only recently have bacterial CE15 members been investigated (711). The only GE protein structure currently deposited with a ligand is St GE2, a variant containing an alanine substitution of the catalytic serine, which is in complex with a methyl ester of the monosaccharide 4- O -methyl glucuronate (4- O -MeGlcA) (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Residue X acid+2 , one of the conserved structural elements that is involved in the coordination of the imidazole ring of the catalytic histidine, is usually a hydrophobic or an aromatic residue located at the entrance of the active site cleft, mostly reviewed for its role in ligand binding [51][52][53][54][55][56] or the release of products of catalysis [51,57]. Consequently, the site-directed mutagenesis of residue X acid+2 in different ABH enzymes has led to various results, which are consistent with its role in ligand binding, including the compromising [52,54,55,58,59] or the enhancement [52] of catalytic activity, the alteration of transport tunnels [57,60], the modification of substrate specificity [53,55,56] and the inversion of enantioselectivity [52]. For the remaining residues that coordinate the imidazole ring of the catalytic histidine, including residue X acid+3 , we have only found a few mutational studies that have resulted in reduced activity [58,61,62], with a single study highlighting the residue's role in the stability of the enzyme and the catalytic activity rather than in ligand binding [58].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%